Dimensions of Service Quality in Badan Penyelenggara Jaminan Sosial Kesehatan Kota Dumai - Evelin, Theovanni Yolanda (KINERJA, 2020)
A business organization as a producer is expected to be able to create products that can satisfy the wants and needs of consumers. Companies that are unable to satisfy consumers will be automatically displaced from competition. However, it is ironic that, in contrast to technology and an increasingly developing era, the implementation of public services is still not in accordance with the needs and desires of the community. The progress of the times has made the order and dimension of community values in various fields more complex. This means that public service activities are currently not ready to respond to community demands. This research was conducted at the BPJS Kesehatan Office in Dumai City. Data sources can be primary and secondary data. Judging from its purpose, this research is a descriptive study, which explains the quality of BPJS Kesehatan Kota Dumai services in conducting services from the point of view of consumers. The results showed that the service at the BPJS Kesehatan Kota Dumai Office still had a number of problems in the service process. In this study, author provide advice to provide training services to employees of the BPJS Kesehatan Kota Dumai and the company is expected to be more responsive to criticism and suggestions from the community to be able to serve the community better.Keywords: Quality, service, community.